2008
DOI: 10.1158/1541-7786.mcr-08-0073
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β–Mediated Tumor Necrosis Factor-Related Apoptosis-Inducing Ligand Expression and Apoptosis in Hepatoma Cells Requires Functional Cooperation between Smad Proteins and Activator Protein-1

Abstract: Transforming growth factor-B (TGF-B) has been shown to induce apoptotic cell death in normal and transformed hepatocytes. We recently identified tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) as an important mediator of TGF-B -induced apoptosis in hepatoma cells. In this study, we have further explored the mechanism by which TGF-B up-regulates TRAIL expression. The 5 ¶-flanking region of the TRAIL gene was isolated and characterized. Deletion mutants of the 5 ¶-untranslated region of the TRAIL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 26 publications
(32 reference statements)
2
21
0
Order By: Relevance
“…This implies that Smad4 expression is critical for the tumor invasion and metastasis of human Hcc, in addition to playing an important role in proliferation and growth. This is consistent with previous reports (20,21), and provides further evidence to suggest that Smad4 plays a key role in Hcc. The present study investigated the effects of Smad4 signaling on the migration of Hcc cells, and the mechanisms behind these effects.…”
Section: Discussionsupporting
confidence: 93%
“…This implies that Smad4 expression is critical for the tumor invasion and metastasis of human Hcc, in addition to playing an important role in proliferation and growth. This is consistent with previous reports (20,21), and provides further evidence to suggest that Smad4 plays a key role in Hcc. The present study investigated the effects of Smad4 signaling on the migration of Hcc cells, and the mechanisms behind these effects.…”
Section: Discussionsupporting
confidence: 93%
“…Agents that induce oxidative stress in spermatozoa cause accumulation of GSSG because the capacity of NADP-dependent GSSG-reducates becomes rate-limiting and the NADPH/NADP ratio decreases. Indeed our results showed that in moderate and severe necrospermia, the rate oxidized glutathione (GSSG) was elevated compared to the control group, and the difference was statistically significant [23][24][25]55]. This confirms the fact that the oxidized form of glutathione is in favored the production of reactive species of oxygen as well as the TGFß1.…”
Section: Discussionsupporting
confidence: 76%
“…Subjects currently on any medication or antioxidant supplementation were not included [16][17][18][19][20][21][22][23][24]. In addition, subjects with testicular varicocele, genital infection, leukocytespermia, chronic illness and serious systemic diseases, smokers and alcoholic men were excluded from the study because of their well-known high seminal ROS levels and decreased antioxidant activity.…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…Specific mutation of these elements abolished TGF-␤1 responsiveness, as well as the binding activity of these factors. The cooperation between Smad and AP-1 transcription factors is essential to determine TGF-␤ signaling to the nucleus, and examples from the literature include the genes encoding endothelin 1 (ET-1), follicle-stimulating hormone ␤ (FSHB), and tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), among others (12,50,51). In fact, AP-1 sites have been shown to be the most enriched motif in Smad2/3 regions identified recently in a ChIP-on-chip analysis (52).…”
Section: Discussionmentioning
confidence: 99%